Analisis Implikasi UU P2SK Terhadap Pemberdayaan UMKM - Adhi Prasetyo Satriyo Wibowo (Pusat Kajian Anggaran, 2023)
Access to financing, which has always been the main problem faced by MSMEs, is expected to be resolved with the PPSK Act. For this reason, this paper aims to analyze the strengthening of MSME empowerment through the PPSK Act. The preparation of this research uses a qualitative approach. The research method used is descriptive using data sourced from various journals, books, laws, and regulations, as well as various other literature related to the title of this research. This study found that the MSME credit ratio has not been able to compete with other business sectors and is also lagging behind other Asian countries. In addition, changes to the MSME criteria as in the Government Regulation on MSMEs have not been followed by adjustments to the credit ceiling for MSMEs. Furthermore, of the 64 MSME empowerment programs implemented in 22 ministries/institutions, according to the author, none has touched on the securities crowdfunding scheme in the MSME empowerment program. On the other hand, the presence of provisions for write-offs and/or write-offs of receivables made the bank's balance sheet healthy again and encouraged banks to extend credit to MSMEs to increase the MSME credit ratio in Indonesia.